Teachers’ Self-efficacy and their Choice of Continuous Professional Development Strategies in Trained Graduate Teachers of NCT Delhi - Maheshwari, Kriti (JOURNAL OF INDIAN EDUCATION, 2022)
The 21st century skills need commitment from professionals to update their knowledge on their own which will in turn help in the development of the students. The Indian government started Massive Open Online Courses (MOOCs) on Study Webs of Active-Learning for Young Aspiring Minds (SWAYAM) portal based on transformative model which is the need of the hour. These types of programmes require motivation for self-learning. Therefore, the researcher administered self-efficacy scale and questionnaire to achieve the objectives of the research on 30 Trained Graduate Teachers (TGTs) teaching in secondary/ senior secondary schools (both government and private) of NCT Delhi. The findings show that no autonomy is given to teachers in choosing the Continuous Professional Development (CPD) programme. The self-efficacy test shows that they are capable enough to take the responsibility for their own Professional Development (PD). Time issues and lack of supportive environment in school caused major hurdles in effective implementation of the CPD strategies.